Integrasi Nilai-Nilai Tauhid, Rahmah, dan Amanah Dalam Model Parenting Islami Kontemporer: Kajian Literatur Kritis - Nurul Fadilah; Najwa Kholida; Masganti (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2025)
This research aims to describe and analyze Islamic values contained in parenting practices and their application in modern Muslim family life. Using a qualitative descriptive approach through the literature study method (library research), this study examines various academic sources such as journals, books, and scientific articles published in 2015–2025. The results of the study show that Islamic parenting is based on the values of monotheism, compassion (rahmah), responsibility (amanah), discipline, honesty, and example (uswah hasanah). These values are the main foundation in shaping the character of children who have faith, noble character, and competitiveness in the global era. The application of Islamic parenting is not only through verbal teaching, but also through habituation, example, and affectionate communication. In the digital age, challenges such as the influence of technology and the difference in values between generations require parents to integrate Islamic principles with modern parenting approaches. Thus, Islamic values remain relevant and can be an effective guideline in forming a harmonious family and a generation of Muslims with noble character and adaptive to the development of the times.